Optimization of Microalgal Harvesting with Inorganic and Organic Flocculants Using Factorial Design of Experiments - Machado, CA (2022)
Microalgae have a lot of potential as a source of several compounds of interest to various industries. However, developing a sustainable and efficient harvesting process on a large scale is still a major challenge. This is particularly a problem when the production of low-value products is intended. Chemical flocculation, followed by sedimentation, is seen as an alternative method to improve the energetic and economic balance of the harvesting step. In this study, inorganic (aluminum sulfate, ferric sulfate, ferric chloride) and organic (Zetag 8185, chitosan, Tanfloc SG) flocculants were tested to harvest Chlorella vulgaris in batch mode. Preliminary assays were conducted to determine the minimum dosages of each flocculant that generates primary flocs at different pH. Except for chitosan, the organic flocculants required small dosages to initiate floc formation. Additional studies were performed for the flocculants with a better performance in the preliminary assays. Zetag 8185 had the best results, reaching 98.8% and 97.9% efficiencies with dosages of 50 and 100 mg L-1, respectively. Lastly, a 2(4) full factorial design experiment was performed to determine the effects of the flocculant dosage, settling time, and mixing time on the Zetag 8185 harvesting efficiency. The harvesting efficiency of C. vulgaris was optimal at a dosage of 100 mg L-1 and 3 min of rapid mixing.